Identification of new urinary metabolites of Byakangelicin, a component of Angelicae dahuricae Radix, in rats - Kwon, OS; Song, YS; Shin, KH; Ryu, JC (PHARMACEUTICAL SOC KOREA, 2003)
Byakangelicin, 9-(2,3-dihydroxy-2-methylbutoxy)-4-methoxy-7H-furo[3,2-g][I]benzopyran-7-one (BKG), a component of Angelicae dahuricae Radix, is considered to be an inhibitor of aldose reductase for the treatment of diabetic cataract. An analytical method for the isolation of BKG developed by high-performance liquid chromatography has been reported. No literature on the metabolism of BKG, however, has been found. With the purpose of identifying new metabolites of BKG, BKG (100 mg/kg) was orally administered to Sprague-Dawley rats via a gavage. Using a metabolic cage, urine was collected for 24 h, and the urine samples were extracted by liquid-liquid extraction. For structural identification of new urinary metabolites of BKG, various instrumental analyses were conducted by gas-chromatography/mass spectrometry, high-performance liquid chromatography/diode array detector, liquid chromatography/mass spectroscopy with thermospray interface and H-1 nuclear magnetic resonance spectroscopy. Two metabolites produced from the C-demethylation or O-dealkylation of BKG were newly identified, and another new but unknown metabolite was assumed to be the hydroxylated form of BKG. These results indicate that the major metabolic products of BKG are formed by O-demethylation or O-dealkylation of BKG side chains.